Shelter Experiences of the Homeless People: “One Wants To Feel Cared For” - Cengizhan Aynacı; Yusuf Genç (İstanbul Üniversitesi Sosyoloji Dergisi)
Homelessness is an increasingly important social problem in Turkey. Research on homelessness in Turkey focuses on issues such as the causes of homelessness, strategies to cope with homelessness, and social services for homelessness. Non-governmental organisations and the framework of the step model largely provide social work practices for homelessness in Turkey. Most of these services are within the scope of pre-housing preventive services and focus on developing coping strategies. For this reason, research on homeless shelters is quite scarce. This study explores the shelter experiences of the homeless and to provide social work recommendations for shelters and homeless individuals based on the findings. Conducted using a qualitative research method and an interpretative phenomenological design, the study’s sample consisted of 30 homeless individuals selected through purposive sampling. The research tool is a semi-structured interview form with questions designed to explore the experiences of homelessness and shelter use. The data obtained from these semi-structured interviews were analysed using descriptive and content analysis methods. The data were examined under three main themes: “mediators,” “challenges,” and “expectations.” Homeless individuals settled in shelters through various means including referrals from other homeless people, environmental actors, shelter staff, security teams, and personal applications. The challenges faced by the homeless in shelters include rules, staff attitudes and behaviours, adaptation, material procurement, inconsistency, technical problems, and access/transportation issues. Expectations from shelters include the provision of psycho-social support units and professional staff, health units within shelters, cleanliness of the shelters, social activities, and a well-organised shelter life. Based on the research findings, it is recommended to adopt spiritually and value-based services in shelters, to improve the content, scope, and services of shelters to better meet the needs of the homeless, to establish psycho-social support and health units within shelters staffed by professional personnel, to create workshops for the homeless, to enhance life skills, and to organise regular social activities.